Effects of Dipole Eddies on Acoustic Propagation in the Northeastern South China Sea - Lu Lu; Feng Nan; Anqi Xu; Xiangqian Liang; Fei Yu (Ocean-Land-Atmosphere Research)
Mesoscale eddies can greatly influence underwater acoustic propagation, which holds substantial academic and practical importance. The impacts of individual cyclonic eddies (CEs) or anticyclonic eddies (AEs) on acoustic propagation have been reported in the global ocean, but the influences of dipole eddies remain unclear. Dipole eddies, with warm-core AE shedding from the Kuroshio loop and cold-core CE on the northeastern side, frequently form in the northeastern South China Sea (SCS). In this study, the effects of 3 pairs of dipole eddies in the northeastern SCS on acoustic propagation were examined via satellite altimeter data, reanalysis data, and a ray tracing model. In general, the AEs were larger and stronger than the CEs. The downwelling in the AEs caused positive sound-speed anomalies, whereas the upwelling in the CEs induced negative sound-speed anomalies. Using the Bellhop ray tracing model, we simulated 5 scenarios of acoustic propagation across dipole eddies by varying the sound source locations and sound propagation paths. The special hydrological and sound-speed structure of dipole eddies resulted in notable variations in the convergence zone and acoustic transmission loss in different scenarios, which were markedly different from those of a single eddy. The findings of this study will contribute to underwater acoustic communication, remote detection, reconnaissance, and counterreconnaissance in the SCS.